Triple negative breast cancer: Early stages management and evolution, a two years experience at the department of breast cancer of CHSF - Nassima, Bouzid; Jessie, Darido; Jed, Diari; Chloe, Dussour; Joel, Ezenfis; Virginie, Cahn; Steven, Guekeu; Luc, Rigonnot (Clinical Journal of Obstetrics and Gynecology, 2020)
Breast cancer is the most common cancer in women and is a major public health problem. It is divided into several subtypes, including triple negatives. The general objective of our study is to establish the profile and the management of patients with triple negative breast cancer over a period of 2 years, operated in our department. During our study period, triple-negative breast cancers accounted for 10% of our population. The most affected age group ranges from 50 to 60. The majority of patients in our sample are pauciparous. In the group of patients who received hormone therapy, it was mainly HRT for 4 to 6 years. 96.77% of patients consulted a health worker within 3 months of the discovery of the signs. Adenopathies are frequently present at the time of diagnosis. 93.54% of the cases have an invasive ductal carcinoma. Triple negative cancers are essentially poorly differentiated. Triple-negative cancer has a high rate of cell renewal. In our study, neoadjuvant chemotherapy is mostly indicated for triple-negative breast cancers ≥ 30 mm at diagnosis and a delayed lumpectomy is then performed in 23.52% of the patients. For tumors of < 30 mm size, a lumpectomy is performed immediately in 76.47% of the patients, followed by adjuvant chemotherapy. Mastectomy was performed in 45.16% of patients; it was mainly indicated in front of a large tumor size associated with a small breast volume, then multifocal breast tumors. Breast reconstruction was performed in 21.42%. Radiation therapy is indicated in the majority of patients, postoperatively. In our population, 11 patients were proposed to have an oncogenetic survey; it was mainly indicated based on the Manchester criteria in front of a young age and a family history of cancer. There are two BRCA 1 mutations, one BRCA 2 mutation, and one case of absence of mutation. The therapeutic intake in case of a mutation is directed towards a prophylactic bilateral mastectomy and adnexectomy, proposed at the age of 40. Two patients had presented triple negative recurrences of their already treated breast cancer; first case PDL1 positive PD-L1 ≥ 1% treated with immunotherapy combined with chemotherapy (atezolizumab/abraxane) while the second and second PDL1 negative treated with chemotherapy alone. Despite their low frequency, triple negative breast cancers represent a subgroup marked by pejorative characteristics, a reserved prognosis, with limited treatment options.